2014
DOI: 10.21055/0370-1069-2014-3-20-24
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the Allocation of Emerging Natural Foci of the Currently Important Infectious Diseases in the West of Kazakhstan

Abstract: Within the period of 2000-2011, in the West of Kazakhstan, identified have been five, previously unknown in the territory, natural foci of dangerous infectious diseases such as hemorrhagic fever with renal syndrome, Astrakhan spotty fever, Crimean hemorrhagic fever, West Nile fever, and tick-borne viral encephalitis. The reason is that key ecological factors for the persistence of the infections in the local biocoenoses occurred. It is characteristic that circulation of the agents of new infectious diseases is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In the West Kazakhstan region from 2001 onwards, the investigation of reservoirs started. These showed the orthohantavirus antigen by ELISA in different species of rodents: bank voles, common voles, forest mice and house mice (Grazhdanov et al, ). Another report demonstrated that rodent tissue suspensions collected in the Almaty region Dzungarian, in the Alatau mountains in 2010–2016, 2.2% (15/684) were positive for orthohantavirus antigens using ELISA (Test system: Hantagnost, Russia), (Sutyagin, Belyaev, Kim, & Berdibekov, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the West Kazakhstan region from 2001 onwards, the investigation of reservoirs started. These showed the orthohantavirus antigen by ELISA in different species of rodents: bank voles, common voles, forest mice and house mice (Grazhdanov et al, ). Another report demonstrated that rodent tissue suspensions collected in the Almaty region Dzungarian, in the Alatau mountains in 2010–2016, 2.2% (15/684) were positive for orthohantavirus antigens using ELISA (Test system: Hantagnost, Russia), (Sutyagin, Belyaev, Kim, & Berdibekov, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some rodent investigations revealed that the natural foci of orthohantaviruses are located between the West Kazakhstan region and Orenburg, the Samara regions of the Russian Federation (Alexeyev, Elgh, Zhestkov, Wadell, & Juto, ; Aminev, Korneev, Slobodenyuk, & Solovich, ; Grazhdanov et al, ). Annual registrations of HFRS in the West Kazakhstan region began in 2000, and a high incidence rate of 16 per 100,000 inhabitants was described in 2005 (Grazhdanov et al, ). In the West Kazakhstan region from 2001 onwards, the investigation of reservoirs started.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term investigations of host reservoirs starting from 2001 by colleagues from the Oral antiplague station revealed natural foci of orthohantaviruses in the floodplains of the Ural River. This area directly borders the Russian Orenburg and Samara regions, where orthohantavirus is also endemic [26,38]. Several small mammals that are also spread in this region such as M. glareolus, M. arvalis, A. uralensis, and M. musculus contained orthohantavirus antigens [26].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1.53% of different species, mostly Myodes glareolus, Microtus arvalis, Microtus minutus, Apodemus uralensis, and Mus musculus were positive. Therefore, so far, natural foci of orthohantaviruses were described in the four northern districts of the West Kazakhstan region (Borili, Bayterek, Shyngyrlau, and Terekti) and very preliminary in the Aktobe region [25,26]. However, in all investigations on orthohantaviruses in West Kazakhstan, contemporary molecular methods were never applied.…”
Section: Introductionmentioning
confidence: 99%